Energy saving on IoT using LoRa: a systematic literature review - Mochammad Haldi Widianto; Arief Ramadhan; Agung Trisetyarso; Edi Abdurachman (International Journal of Reconfigurable and Embedded Systems (IJRES), 2022)
The development of devices connected to the internet is very significant, encouraging the creation of the internet of things (IoT). With remote systems, IoT is not enough to use in case of internet instability. By using long range (LoRa), IoT systems can now solve this problem. Millions of data make IoT-LoRa have to spend a lot of energy. This paper helps discover where recent studies offer a broad perspective on energy savings using the systematic literature review (SLR). The paper extracted 252 articles from IEEE, ACM, MDPI, Springer, Hindawi, ScienceDirect, and IAES. 44 articles passed the specified inclusion and exclusion criteria. The article focuses on knowledge about IoT-Lora, energy saving needs, energy saving factors, and the paper demographics. The author synthesizes studies for that purpose on IoT applications using LoRa.